Efficacy and safety of immune checkpoint inhibitors as neoadjuvant therapy in perioperative patients with non-small cell lung cancer: a network meta-analysis and systematic review based on randomized controlled trials - Chen, Kaiqi; Wang, Xinwei; Yue, Rui; Chen, Wei; Zhu, Danping; Cui, Shikui; Zhang, Xijian; Jin, Zhao; Xiao, Tong (Frontiers in Immunology, 2024)
Background: Presently, numerous perioperative immunotherapy regimens centered around the integration of ICIs and chemotherapy have undergone clinical trials.Nonetheless, due to the absence of direct comparative RCTs among these treatment regimens, this study aims to employ Bayesian network meta-analysis to ascertain the optimal combination of ICIs and chemotherapy.Methods: A systematic literature search was conducted in PubMed, EMBASE, Cochrane Library, Web of Science databases, and major international conference publications up to April 10, 2024. This comprehensive search yielded a total of 1434 studies. Following a rigorous screening process that involved evaluating the studies for relevance, methodological quality, and alignment with our research objectives, 8 studies were carefully selected for inclusion in the final analysis. Based on these curated search results, a systematic review and network meta-analysis were conducted.Results: 8 RCTs were included, encompassing 7 treatments and involving 3699 operable NSCLC patients at stages I-III. Compared to chemotherapy alone, perioperative immunotherapy demonstrated higher efficacy.The combination of toripalimab and chemotherapy showed the most significant improvement in event-free survival ( HR= 0.40). The regimen that most notably enhanced overall survival was Nivolumab combined with chemotherapy (HR = 0.62). In terms of pathological complete response, the combination of Toripalimab and chemotherapy exhibited the highest benefit (OR = 32.89). Regarding the improvement in R0 resection, Pembrolizumab plus chemotherapy performed most prominently(OR=2.15). In terms of the incidence of grade 3 or higher adverse events, durvalumab combined with chemotherapy had the lowest incidence (OR = 1.05), while the incidence for other regimens was higher than chemotherapy alone.The efficacy of perioperative immunotherapy plus chemotherapy in patients with early NSCLC is significantly improved compared to chemotherapy alone. Although there is a certain risk of adverse events, the safety is within a controllable range. After a comprehensive evaluation of five endpoints in this study, it is believed that the combination of Toripalimab or Nivolumab with chemotherapy may be the optimal immunotherapy regimen for the treatment of stage Ib-IIIb NSCLC. These findings will help guide the design of clinical treatment plans and ICIs selection.